(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In the article in the linguо-cultural aspect the somatic lexical-phraseological sphere of the Belarusian people is interpreted; the essence of the term “somatizm” is determined; the stereotypes of the Belarusian somatic phraseology are researched. The national-cultural information of the phraseological units is revealed and stereotypes which are encoded in the inner form of the phraseological units are fixed and decoded. The results of the research demonstrate that stereotypes can be shown not only through the Belarusian complex idea about people but of exactly through the phraseological components, which are used in the stereotype situation. For example, generosity and hospitable are the distinguishing features of the Belarusian mentality, which are illustrated in the phraseological units з распасцёртымі рукамі (прымаць, сустракаць, чакаць) ‘cordiality, with hospitality and great pleasure’; шчодрай рукой (раздаваць, надзяляць, дапамагаць і пад.) ‘without avidity’ etc.; stereotype situation ‘display of emotion’ is illustrated in the phraseological units галава баліць / балела ‘someone worries about somebody or something, is alarmed, feels nervous’; галава гарыць / гарэла ‘someone is upset, worried’ etc. Linguistic meaning and cultural content of the phraseological units cause their special role in the speaking – to characterize the person’s attitude to somebody or something and pay attention to the different ways of their display. The national-cultural interpretation of the lexical-phraseological sphere of the Belarusian people shows that to imagine the part of their language picture of the world could be exactly through the description of the stereotypes in the inner form of the phraseological units.